Moral psychology in the Qur’an: behavioral patterns of believers, disbelievers, and hypocrites and their contemporary significance - Osmani, Noor Mohammad; Md Motiur Rahman, Abul Kalam (RSIS International, 2025)
This study examines the Qur’anic portrayal of human behavior through a moral-psychological analysis of three central character types: believers, disbelievers, and hypocrites. While classical Qur’anic exegesis has long described these groups in terms of theological and ethical identity, contemporary contexts demand a renewed exploration of their behavioral patterns, psychological dispositions, and relevance to modern society. Drawing on thematic analysis of selected Qur’anic verses and major tafsīr works—including those of al-Ṭabarī, Ibn Kathīr, al-Qurṭubī, and al-Rāzī—this article identifies the core traits that define each behavioral category. Believers are characterized by sincerity, moral consistency, resilience, and a deep consciousness of God (taqwā). Disbelievers exhibit denial, arrogance, resistance to truth, and spiritual blindness, while hypocrites display behavioral duality, inconsistency, deception, and cognitive dissonance. The article further conducts a comparative evaluation of these profiles, highlighting their psychological and ethical dimensions. Special attention is given to the manifestation of these Qur’anic character types in contemporary society, including the rise of moral relativism, identity crises, spiritual instability, and performative religiosity. This study argues that the Qur’an offers a comprehensive framework for understanding human moral behavior that remains profoundly relevant in addressing modern ethical dilemmas, community challenges, and youth identity formation. The findings contribute to Qur’anic moral psychology by bridging classical scriptural insights with current behavioral realities, demonstrating the enduring relevance of the Qur’an’s guidance for individual transformation and social well-being.